The Influence Of Diversity And Inclusion On Employee Performance With Organisational Culture As An Intervening Variable At PT XYZ - Lukiyana, Lukiyana; Diansyah, Diansyah; Cahyanto, Budhi (Jurnal Fokus Manajemen, 2025)
This study aims to analyse the effect of diversity and inclusion on employee performance at PT XYZ, with organisational culture as an intervening variable. The background of this study is based on the importance of diversity management and the creation of an inclusive work environment in improving individual and organisational performance. This study employs a quantitative approach using Partial Least Squares Structural Equation Modelling (PLS-SEM) to test the relationships between variables. The research was conducted in several stages, starting from literature and theory exploration, data collection from the research subjects, data validity testing using reliability and validity tests, data processing, and hypothesis testing. The data was analysed using the SmartPLS 4.0 application, with a sample size of 322 respondents. The results of the study indicate that diversity influences employee performance, but inclusion does not influence employee performance. Meanwhile, organisational culture has been proven to significantly moderate the relationship between diversity and inclusion on performance. These findings emphasise the importance of companies building a supportive and conducive work culture, so that the values of diversity and inclusion can be fully integrated into every work process. With a positive organisational culture, diversity and inclusion are not merely symbols or formal policies but genuinely drive collaboration, innovation, and productivity, thereby contributing to sustained improvements in employee performance.